2021
DOI: 10.1093/gbe/evab221
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Gene Expression and Chromatin Regulation during Hydra Head Regeneration

Abstract: The cnidarian model organism Hydra has long been studied for its remarkable ability to regenerate its head, which is controlled by a head organizer located near the hypostome. The canonical Wnt pathway plays a central role in head organizer function during regeneration and during bud formation, which is the asexual mode of reproduction in Hydra. However, it is unclear how shared the developmental programs of head organizer genesis are in budding and regeneration. Time-series analysis of gene expression changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 81 publications
2
42
0
Order By: Relevance
“…Taken together, these results suggest PaxC has a role in patterning during head regeneration. Supporting this is the enrichment of Pax5 and Pax6 binding motifs for dynamic accessibility during Hydra head regeneration (Murad et al, 2021). These binding motifs are annotated for known vertebrate motifs, so the Hydra binding factor remains to be confirmed.…”
Section: Scrna-seq Clarifies Bulk Rna-seq Results By Confirming Cell-...mentioning
confidence: 98%
See 4 more Smart Citations
“…Taken together, these results suggest PaxC has a role in patterning during head regeneration. Supporting this is the enrichment of Pax5 and Pax6 binding motifs for dynamic accessibility during Hydra head regeneration (Murad et al, 2021). These binding motifs are annotated for known vertebrate motifs, so the Hydra binding factor remains to be confirmed.…”
Section: Scrna-seq Clarifies Bulk Rna-seq Results By Confirming Cell-...mentioning
confidence: 98%
“…We found binding motifs in the promoter for homeodomain, C2H2 zinc finger, basic helix-loop-helix (bHLH), and Highmobility group (HMG) domain factors that match TFs such as including Sox11 and Six3/6 (or Optix) (Table S5). Using only hypostome data that we previously generated (Murad et al, 2021), we found transcription factor binding motifs in the Wnt3 promoter for the Sox family (Sox2, Sox11, Sox13, Sox17, Sox18), and Six3/6 (Table S5).…”
Section: Wnt3 Cis-regulationmentioning
confidence: 99%
See 3 more Smart Citations